Physiological responses and transcriptomic analysis of StCPD gene overexpression in potato under salt stresses - Zhou, Xiangyan; Ma, Yanming; Miao, Rong; Li, Caijuan; Liu, Ziliang; Zhang, Dan; Chen, Sijin; Luo, Jiaqi; Tang, Wenhui (Frontiers in Plant Science, 2024)
The potato (Solanum tuberosum L.), one of the most vital food crops worldwide, is sensitive to salinity. Brassinosteroids (BRs) are crucial in tolerance to various abiotic stresses. The constitutive photomorphogenesis and dwarf (CPD) gene encodes C-3 oxidase which is a rate-limiting enzyme that controls the synthesis of BRs. In this study, we used StCPD gene overexpression (T) and untransgenic (NT) plants obtained from our former research to illustrate adaptive resistance to salt stress at levels of phenotype, cell ultra-structure, physiology and biochemistry, hormone and transcription. Results showed the accumulation of 2, 4-epibrassionolide (EBL) in T potatoes. We found under high salt situations, the changed Na + /K + transporter genes expression was linked with the prevalent ionic responses in T plants, which led to lower concentrations of K + and higher concentrations of Na + in leaves. Furthermore, RNA-sequencing (RNA-seq) data elucidated that gene expressions in NT and T plants were significantly changed with 200 mM NaCl treatment for 24 h and 48 h, compared with 0 h treatment. Functional enrichment analysis suggested that most of the differentially expressed genes (DEGs) were related to the regulation of BRs related gene expression, pigment metabolism process, light and action and plant hormone signal transduction. These findings suggested that StCPD gene overexpression can alleviate the damage caused by salt stress and enhance the salt resistance of potato plantlets. Our study provides an essential reference for further research on BRs regulation of plant molecular mechanisms in potatoes with stress tolerance.